Pengaruh Model Pembelajaran Berbasis Proyek Terhadap Kemampuan Siswa Menulis Slogan - Herman Didipu; Alit Renaldi Harun (PT Cendekia Education Center, 2026)
This study aims to examine the impact of the Project Based Learning (PjBL) learning model on the ability to write slogan texts in grade VII students of MTs Negeri 2, Gorontalo Regency. The main problem identified in this study is the lack of students' ability to write ideas and messages in a creative way. This study uses a quantitative approach with a One Group Pretest-Posttest design. The research sample consisted of 21 students taken using a saturated sampling technique. Data were collected through a writing ability test assessed based on the rubric of content, language, creativity, and neatness. The results of descriptive statistics show an increase in the average score from 46.00 (pre-test) to 80.48 (post-test). The results of the Wilcoxon Signed Ranks Test show that all students (n=21) experienced a significant increase in scores (Positive Ranks) with a significance value that meets the criteria for accepting the hypothesis. The conclusion of this study shows that the PjBL model has a significant effect on students' ability to write expressions and messages creatively in the form of slogan texts. This model is recommended as an effective solution to improve creative writing skills at the Madrasah Tsanawiyah level.